(3TQM bWQ GdfOi hHd GdUOis - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s
(3ChdgG (B:s
... (3CeG HYO agPg fcJ MQQJgG Ydi ebOeJj GdeSeGI HbWQ GdfOi hHd GdUOi QGaYI dMLGHgG cGTaI dfbGHgG ecedI dThGgOgG eJeeI dahGFOgG cGajI def GbJUQ YdjgG hGajI HHZjI ef LfM ef WdGH Yde GdYQHjI EdjgG (B,,,s
(3BNQgG (B:s
.. (3hEfeG de jaYdhG Pdc dFdG jdJHS HGdeVGQY GdeHOhA HGdgeRI aj MGdI Gdhba hefgG eG jcSQ dG ZjQ hgh GdHGbj hPdc CUd GdHGH hgPG CNgQ eG CQOJ (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\ 147s
(3cTa GdXfhf (B2\ 1352s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs